Sistemas nacionais de inovação e direitos de propriedade industrial: notas introdutórias a um debate necessário - Albuquerque, Eduardo da Motta e (Estudos Econômicos (São Paulo), 1996)
Different national systems of innovation (NSIs) have different intellectual property rights (IPRs) legislations. The connections of the patent laws with the economic factors are established. The analysis of the patent system economics is the starting point, specially the trade off between the incentives to innovate or to diffuse innovations. Different mix of these incentives may create different economic environments. The now developed countries built their IPR legislations in accordance with the specific characteristics of the formation of their NSIs. To analyze the Brazilian case, three aspects are shown: 1) the growing role performed by knowledge and information in the economic process; 2) the recent international pressures for tighter IPRs; 3) the present situation of the Brazilian NSI.